(untitled) (Global Journal of Human-Social Science, 2018)
The study was carried out in Segbewema Njaluahun Chiefdom of the Kailahun District in the Eastern Region of Sierra Leone Segbewema is the Administrative Center of the Njaluahun Chiefdom where vegetable gardening is done on an appreciable scale especially by women both in the dry and the rainy seasons The study adopted a case study to explore the impact of extended family ties on the academic performance of children in Segbewema The study sample comprised of 60 respondents made up of 30 teachers 5 traders 5 commercial motor bike riders 5 NGO workers and 15 pupils The major instruments used to collect data for this study were questionnaire interview and personal observation Questionnaires were divided into six sections to reflect each objective The questions were pretested to ascertain the uniformity of items The data collected from the questionnaires interviews and observation were analyzed both quantitatively and qualitatively The quantitative data was analyzed in tables and percentages and qualitative data was analyzed in narrative form Sierra Leone has a projected population of about 7 100 000 by the provisional result of the 2015 National population and Housing Census and with a predominately extended family structure that has the likelihood to be impacted with disadvantages associated with the family tie system